Teaching Mathematics through Virtual Learning Objects at Universidad Católica de Pereira (2019)
This article presents the results of a research carried out in order tomotivate students in the learning process of mathematics through the useof Virtual Learning Objects (OVA) and having as a significant departureteaching practices based in context, since it is one of the areas havinghigher academic mortality in educational institutions in our country.The aim is to transform some teaching practices in this area and developa Virtual Learning Object to be used as a motivating axis among student -teacher - discipline and to provide the student with the acquisition of skills,competences, and abilities inherent to those proposed by the NationalMinistry of Education.It is very important to consider that the design and construction of theOVA is a fundamental aspect when appropriating a methodology thataims to consolidate mathematical concepts and specific knowledge in thestudents.An aspect taken into account when designing these “objects” is that thestudents use this resource as much as possible; that is why they mustbe developed with specifications of adaptability, accessibility and easynavigation